Modeling of plasma motion in a toroidal solenoid - Tu, Yuqiang. (2009)
Filtered Cathodic Vacuum Arc (FCVA) deposition technique has received extensive attention recently due to its unique feature: vacuum arc is generated at one end of a toroidal solenoid filter, in which those ions and electrons in the arc follow the force line of the magnetic field and pass through, while those neutral particles moving in straight lines are filtered away, and a "purified" plasma is obtained at the other end. Thin films, such as to-carbon films prepared by this method exhibit superior properties. In order to understand the plasma behavior in this curved magnetic field, a guiding center (gc) drift model was proposed by some researchers based on the Newton's Law, the Maxwell equations and the self-consistent effect. But it was not quantity-effective. Experiment evidence shows that there is an electric potential difference between the center and the wall of the duct.